2020
DOI: 10.1029/2019jd031535
|View full text |Cite
|
Sign up to set email alerts
|

Individual Particle Characteristics, Optical Properties and Evolution of an Extreme Long‐Range Transported Biomass Burning Event in the European Arctic (Ny‐Ålesund, Svalbard Islands)

Abstract: This paper reports an exceptional biomass burning (BB) advection event from Alaska registered at Ny‐Ålesund from 10 to 17 July 2015 with particular interest on the influence of the airborne particle characteristics on the optical properties of the aerosol during the event. To this purpose we considered two DEKATI 12‐stage aerosol samples spanning the entire advection and analyzed them by scanning electron microscopy techniques. Aerosol chemical data and microphysical properties were also evaluated in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 79 publications
1
13
1
Order By: Relevance
“…The fly-ash particles and primary particles of Fe aggregates commonly exhibited spherical shapes, which indicated that they formed through rapid cooling after melting or evaporation at high temperatures during emission. The shape and composition of the Fe aggregates are consistent with those observed near sources in East Asia (Moteki et al, 2017). Moteki et al, showed that Fe-aggregate particles consist of magnetite, which absorbs light and imposes warming effects on the climate.…”
Section: Fly-ash and Fe-aggregate Inclusionssupporting
confidence: 70%
See 2 more Smart Citations
“…The fly-ash particles and primary particles of Fe aggregates commonly exhibited spherical shapes, which indicated that they formed through rapid cooling after melting or evaporation at high temperatures during emission. The shape and composition of the Fe aggregates are consistent with those observed near sources in East Asia (Moteki et al, 2017). Moteki et al, showed that Fe-aggregate particles consist of magnetite, which absorbs light and imposes warming effects on the climate.…”
Section: Fly-ash and Fe-aggregate Inclusionssupporting
confidence: 70%
“…We also use the term "BC" instead of "soot" in the model simulations and for the results from those instruments that measure BC by assuming that soot and BC are qualitatively the same material. An individual Fe-aggregate particle usually consists of more than two spherical Fe-oxide (magnetite) particles (Moteki et al, 2017;Ohata et al, 2018;Kurisu et al;Li et al, 2017). Fe-aggregate particles mainly originate from anthropogenic sources (Moteki et al, 2017).…”
Section: Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the events are characterized by aerosol mass concentrations not exceeding 4 µg/m 3 , with only one main exception being represented by the peak event registered on 10-14 July. This latter coincided with an extreme wildfire biomass burning advection event from the Yukon-Koyukuk taiga region that affected the Svalbard archipelago in mid-July 2015, with some aerosol persisting in the stratosphere for at least one month after the advection [33,34]. The daily chemical data contributing to the probability plots were extrapolated in order to distinguish the main dust events over Ny-Ålesund based on their sources.…”
Section: Dust Sources and Dust Eventsmentioning
confidence: 99%
“…In 2000, the energy production sector (including fossil fuels and solid residential fuels combustion) generated approximately 59 % of the total global BC emissions, while the remaining came from biomass burning (Bond et al, 2013). BC particles are characterized by a mass size distribution peaking around 100-250 nm (or mass equivalent diameter), e.g., 240 nm in the Svalbard area in spring (Bond et al, 2013;Laborde et al, 2013;Zanatta et al, 2016;Motos et al, 2019). The impact of BC particles absorbing the incoming solar radiation has indeed a non-negligible role in the Arctic region, which is already threatened by a twofold temperature increase compared to the mid-latitude areas, the so-called "Arctic amplification" (Bond et al, 2013;Cohen et al, 2014;Serreze and Barry, 2011).…”
Section: Introductionmentioning
confidence: 99%